Answer:
Each hiker receives 7 ounces of trail mix
Step-by-step explanation:
Trail mix=quantity of peanuts+quantity of raisins+quantity of walnuts+quantity of chocolate chips
where;
Quantity of peanuts=1.25 pounds
Quantity of raisins=14 oz, since 1 pound=16 oz.
Quantity of raisins=(14/16)=0.875 pounds
Quantity of walnuts=12 oz=(12/16)=0.75 pounds
Quantity of chocolate chips=10 oz=(10/16)=0.625 pounds
Replacing;
Trail mix=(1.25+0.875+0.75+0.625)=3.5 pounds
Trail mix=Quantity per hiker×Number of hikers
where;
Trail mix=3.5 pounds
Quantity per hiker=q
Number of hikers=8
Replacing;
3.5=q×8
q=3.5/8=0.4375 pounds
I pound=16 ounces
q=0.4375×16=7 ounces
Each hiker receives 7 ounces of trail mix
Part A)
The table doesn't represent y as a function of x.
Why? <span>One reason is that 1 or 3 is the first element in more than one ordered pair.
Part B)
f(x) = 10x + 20
f(120)= 10*120 + 20 = 1200 + 20 = 1220
</span><span>f(120) represents cost of boating for 120 hours.</span><span>
</span>
^n=1/square root of 59 (535) ,if that makes sense its hard to type it
Answer:
![\left(-t^4-5t^3-10t^2\right)+\left(9t^3+3t^2-1\right)=-t^4+4t^3-7t^2-1](https://tex.z-dn.net/?f=%5Cleft%28-t%5E4-5t%5E3-10t%5E2%5Cright%29%2B%5Cleft%289t%5E3%2B3t%5E2-1%5Cright%29%3D-t%5E4%2B4t%5E3-7t%5E2-1)
Step-by-step explanation:
Given the expression
![\left(-t^4\:-5t^3\:-10t^2\:\right)+\left(9t^3\:+3t^2\:-1\right)](https://tex.z-dn.net/?f=%5Cleft%28-t%5E4%5C%3A-5t%5E3%5C%3A-10t%5E2%5C%3A%5Cright%29%2B%5Cleft%289t%5E3%5C%3A%2B3t%5E2%5C%3A-1%5Cright%29)
Remove parentheses: (a)=a
![=-t^4-5t^3-10t^2+9t^3+3t^2-1](https://tex.z-dn.net/?f=%3D-t%5E4-5t%5E3-10t%5E2%2B9t%5E3%2B3t%5E2-1)
Group like terms
![=-t^4-5t^3+9t^3-10t^2+3t^2-1](https://tex.z-dn.net/?f=%3D-t%5E4-5t%5E3%2B9t%5E3-10t%5E2%2B3t%5E2-1)
Add similar elements
∵ ![-10t^2+3t^2=-7t^2](https://tex.z-dn.net/?f=-10t%5E2%2B3t%5E2%3D-7t%5E2)
Add similar elements
∵ ![-5t^3+9t^3=4t^3](https://tex.z-dn.net/?f=-5t%5E3%2B9t%5E3%3D4t%5E3)
Thus, the equivalent expression in simplified form:
![\left(-t^4-5t^3-10t^2\right)+\left(9t^3+3t^2-1\right)=-t^4+4t^3-7t^2-1](https://tex.z-dn.net/?f=%5Cleft%28-t%5E4-5t%5E3-10t%5E2%5Cright%29%2B%5Cleft%289t%5E3%2B3t%5E2-1%5Cright%29%3D-t%5E4%2B4t%5E3-7t%5E2-1)
Answer:
If b=-3 then the first expression is equal to 24 and the second expression is equal to -14.
If b=-2 then the first expression is equal to 8 and the second expression is equal to -36.
If b=10 then the first expression is equal to 440 and the second expression is equal to 324.
Yes, it is true.
Step-by-step explanation:
b=-3:
4b(b+1)=4(-3)(-3+1)=-12(-2)=24
(2b+7)(2b-8)=(2(-3)+7)(2(-3)-8)=(-6+7)(-6-8)=1(-14)=-14
b=-2:
4b(b+1)=4(-2)(-2+1)=-8(-1)=8
(2b+7)(2b-8)=(2(-2)+7)(2(-2)-8)=(-4+7)(-4-8)=3(-12)=-36
b=10:
4b(b+1)=4(10)(10+1)=40(11)=440
(2b+7)(2b-8)=(2(10)+7)(2(10)-8)=(20+7)(20-8)=27(12)=324